2007
DOI: 10.1038/nbt1300
|View full text |Cite
|
Sign up to set email alerts
|

A high-quality catalog of the Drosophila melanogaster proteome

Abstract: Understanding how proteins and their complex interaction networks convert the genomic information into a dynamic living organism is a fundamental challenge in biological sciences. As an important step towards understanding the systems biology of a complex eukaryote, we cataloged 63% of the predicted Drosophila melanogaster proteome by detecting 9,124 proteins from 498,000 redundant and 72,281 distinct peptide identifications. This unprecedented high proteome coverage for a complex eukaryote was achieved by com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
233
0
4

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 249 publications
(247 citation statements)
references
References 26 publications
(21 reference statements)
10
233
0
4
Order By: Relevance
“…Sequencing of the genome has fostered various initiatives to catalog the proteome of genetic model organisms such as yeast (37), Caenorhabditis elegans (38), Drosophila (39,40), and the mouse (41). Similarly a collaborative program has been established to explore systematically the human proteome (42,43).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sequencing of the genome has fostered various initiatives to catalog the proteome of genetic model organisms such as yeast (37), Caenorhabditis elegans (38), Drosophila (39,40), and the mouse (41). Similarly a collaborative program has been established to explore systematically the human proteome (42,43).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly alternative splicing and overlapping genes present particularly complex annotation problems, and indeed, some estimates suggest that the majority of genes undergo alternative splicing (51,52). Direct mass spectrometric identification of peptide sequences can resolve such ambiguities (40) as it generates an independent line of evidence at the translational level with error sources distinct from nucleotide-based approaches. Here we provided rigorous peptide level evidence for ϳ1500 genes of the zebrafish genome.…”
Section: Fig 1 Estimated Sensitivity and Error Of Protein Identificmentioning
confidence: 99%
“…Recently, several research groups have already taken advantage of shotgun proteomic data to improve annotated genomes, including Homo sapiens, 44 Arabidopsis thaliana, 45 Drosophila melanogaster, 46 and Caenorhabditis elegans. 47 It is consistently reported that many peptides were mapped to genome sequences not considered as transcription regions previously.…”
Section: Discussionmentioning
confidence: 99%
“…Ideally, the spectral library should be generated on a MS instrument similar to the one used to acquire further SWATH-MS data as the correlation of the fragment intensities for a peptide acquired on different instrument was shown to be rather low [10]. Although Rosenberger et al recently published a library containing assays for 10,000 human proteins [9] and deep libraries for other applications such as SRM (Selected Reaction Monitoring) have been generated [11][12][13], the number of publicly available spectral libraries for SWATH-MS is still limited. Several other studies have produced libraries for other species [14][15][16].…”
mentioning
confidence: 99%